Impact of a tropical monsoon climate on formaldehyde exposure and microbial contamination in anatomy dissection hall - Areeya Madsusan; Saowaluk Krainara; Wantanasak Suksong; Kittithat Sudchoo; Nadeyah Tohmoh; Pattharaporn Jonggrijug; Chomkaeo Maipunklang; Chanitsara Chadaram; Kholeeyoh Samaeng; Piyadhida Kurdthongmee; Uratit Noosab; Arun Nakapong; et al. (PLoS ONE, 2025)
Gross anatomy dissection is an essential component of medical and health science education, yet it presents notable occupational hazards, particularly from formaldehyde (FA) exposure and microbial contamination. These risks may be intensified in anatomy dissection halls located in tropical monsoon (Am) climates, where elevated humidity and temperature promote both chemical volatility and microbial persistence. This study assessed the combined effects of such climatic conditions on FA concentrations and microbial ecology within a naturally ventilated dissection hall in southern Thailand. FA levels were measured through personal and area air sampling across seven anatomical regions, while microbial contamination on cadaver-contact surfaces was evaluated using culture-based methods and high-throughput sequencing. Functional prediction of microbial communities was performed using PICRUSt2 to assess their metabolic adaptation to environmental stressors. The results revealed that both personal and indoor FA concentrations (mean 1.17 ± 0.39 ppm and 1.09 ± 0.45 ppm, respectively) exceeded several international occupational exposure limits, with the highest levels observed during dissections involving deep or adipose-rich anatomical regions. Microbial analyses identified stress-tolerant and potentially pathogenic genera, including Bdellovibrio , Aequorivita , and Aspergillus spp. , along with enriched pathways involved in aromatic compound degradation and environmental resilience. These findings highlight the limitations of natural ventilation in controlling occupational exposures and microbial contamination in Am climate anatomy laboratories. The study supports the implementation of climate-responsive engineering controls and laboratory management strategies that address chemical safety, thermal regulation, and biosafety to promote healthier and more sustainable dissection environments in similar high-risk settings.